Soluções tecnológicas ecoeficientes para o desenvolvimento sustentável: uma análise teórico-conceitual - Leandro, Luiz Alberto de Lima; Neffa, Elza Maria (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The environmental issue involves the meaning of quality of life and well- being of nations that seem to be associated with economic growth and consumption. The environmental issue is a development dimension and should be considered at all levels of decision making in the political scenario. This paper presents a reflection on the issue of sustainable development and the contradictions present in the indication of purely technological solutions as strategies for overcoming the environmental crisis. As an alternative to purely technological solutions the concept of eco-development arises, as a way out of the development model that uses economic growth basically as a single measure of efficiency. We believe that environmental management committed to public planning oriented towards an emancipatory ideal is able to contribute to building sustainable societies. Even if we develop eco-efficiency, ecological modernization, sustainable development and the green economy, such techniques alone do not seem to provide effective solutions that generate a type of development that can promote structural changes in the system in terms of public policies and new ways of understanding and dealing with the theme of economic growth.